Pemberdayaan Masyarakat Desa melalui Edukasi Pengantar Bisnis Berbasis Potensi Lokal untuk Pengembangan Usaha Produktif - Mirza; Mulyadi; M. Yusuf; Sri Yanna; Zalikha; Emalia Ariska; Zuriani Ritongag; Novida Humairah (Jurnal Pengabdian Pemersatu Bangsa, 2026)
Community empowerment through the development of productive businesses based on local potential is an effective strategy for strengthening rural economic independence. However, limited knowledge of basic business management remains a major challenge for many rural communities in developing sustainable enterprises. This community service program aimed to improve the knowledge and entrepreneurial skills of the residents of Blang Bladeh Village by providing business introduction education based on local resources. A participatory approach was employed involving 26 community members as participants. The program consisted of four stages: needs assessment, business education, business planning assistance, and program evaluation. The training materials included business opportunity identification, product development, marketing strategies, basic financial management, and the utilization of digital media for business promotion. The results demonstrated that participants improved their understanding of fundamental business concepts, became more capable of identifying local economic opportunities, and successfully developed simple business plans based on local resources. The program also encouraged participants to adopt more systematic business management practices, improve product innovation, and recognize the importance of digital marketing in expanding market access. Furthermore, active participation throughout the program strengthened community motivation to develop sustainable productive businesses. Overall, the implementation of local potential-based business education proved to be an effective community empowerment strategy for enhancing entrepreneurial capacity and supporting sustainable rural economic development